Metathesis polymerization adhesives and coatings - KENDALL JONATHAN L; CASTER KENNETH C (2004)
An adhesive or coating composition prepared by mixing together at least one metathesizable highly-reactive cycloolefin (e.g., a norbornadiene) and a metathesis catalyst. The use of highly-reactive cycloolefins can provide exceptional adherence to a low-surface-tension substrate. Another embodiment is a two-part adhesive or coating system wherein the first part includes at least one first metathesizable material, and the second part includes at least one liquid metathesis oligomer or polymer and a metathesis catalyst.